Ecotoxicological assessment of sediments from the Port of Santos and the disposal sites of dredged material - Sousa, Eduinetty Ceci P. M.; Abessa, Denis Moledo de Souza [UNESP]; Bauer R. F., Rachid; Gasparro, Marcia R.; Zaroni, Letícia P. (Universidade de São Paulo (USP), Instituto Oceanográfico, 2007)
A dragagem dos sedimentos do Canal de Santos é necessária para permitir o trânsito de navios que operam no Porto de Santos. As áreas de disposição do material dragado estão situadas na zona costeira, em frente à Baía de Santos. Este estudo visou avaliar a qualidade dos sedimentos do Canal de Santos e das áreas de disposição atuais e antigas, utilizando testes de toxicidade de sedimento integral com anfípodos e de toxicidade de elutriatos com embriões de ouriço do mar. As amostras do Canal de Santos foram consideradas as mais tóxicas: todas as amostras dessa área foram consideradas significativamente tóxicas. Além disso, algumas amostras das áreas de disposição exibiram toxicidade. Os resultados mostraram, portanto, que os sedimentos apresentam evidências de degradação em sua qualidade, porém novos estudos devem ser conduzidos visando determinar as relações entre contaminação e toxicidade. Os resultados sugerem ainda que a disposição dos sedimentos dragados deva ser reavaliada.

The dredging of sediments from the Santos Channel is necessary to allow the navigation of ships operating in the Port of Santos. The disposal sites for such sediments are situated on the coastal zone, in front of the Santos Bay. The present paper aimed at evaluating the toxicity of sediments collected at the Santos Channel and at the former and current sediment disposal sites. Whole sediment tests with amphipods and elutriate assays with sea-urchin embryos were used. The samples from the Santos Channel were considered the most toxic: all the sediment samples from this area showed toxicity. Moreover, some samples from both former and new sediment disposal sites exhibited toxicity. Therefore, results showed that sediments from the studied areas present evidences of degradation; however, further studies are required to determine relationships between toxicity and contamination. Results also suggested that the disposal of dredged sediments should be re-evaluated.
Keywords: Santos; Porto de Santos; Sedimento; Toxicidade; Dragagem; Santos; Port of Santos; Sediment; Toxicity; Dredging